Brand-Evoked Mental Imagery: The Role of Brands in Eliciting Mental Imagery - Diana Gavilan; Maria Avello (SAGE Open, 2020)
This research provides evidence of the role played by a brand in the stimulation of mental imagery. We anticipate that a familiar (vs. unfamiliar) brand will evoke higher levels of visual mental imagery in the consumer. In addition, if the consumer exhibits favorability toward the brand, the visual mental imagery evoked will be enhanced. Therefore, we provide evidence of the moderating role of brand favorability in the relationship between brand familiarity and visual mental imagery. Our findings suggest that brands are evocative and are able to enhance (or reduce) information processing and, thus, the generation of visual mental images that we name “brand-evoked mental imagery.” The results contribute to the literature on branding and mental imagery and have several practical implications for marketers.